Three-State Quantum Heat Engine Based on Carnot Cycle - Trengginas Eka Putra Sutantyo (Universitas Andalas, 2020)
In this paper,we consider three models of quantum heat engines based on Carnot cycle using three energy levels; (1) the ground state, (2) the degenerate state, and (3) the highest energy state. We investigate the variation in the transition state by selecting three different degenerated states. The result we obtained still analogous with the classical heat engine efficiency and also the previous Quantum Carnot Engine model, which only depends on the initial width and the final width of the potential well in isothermal expansion. Moreover, the effect of transition state generally can be accepted for multistate quantum heat engines with 3D systems in cubic potential.